2010
DOI: 10.1111/j.2042-3306.2010.00141.x
|View full text |Cite
|
Sign up to set email alerts
|

Cross-sectional area of the tendons of the tarsal region in Standardbred trotter horses

Abstract: The establishment of reference values could serve as a tool to discriminate between normal and abnormal dimensions of tarsal tendons in STH. Other horse breeds should need their own reference values.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 20 publications
1
8
0
Order By: Relevance
“…Our findings are consistent with the results reported by other authors, confirming that better results are obtained when a linear probe is used for tendon examination in dogs and horses (Long and Nyland 1999;Bruce et al 2000;Kramer et al 2001;Agut et al 2009;Vilar et al 2011;Spinella et al 2013). Moreover, ultrasonographic findings confirmed the biological inactivity and biocompatibility of stainless steel AISI 316L, and revealed minimal tissue reaction of fibre tendon around it, with no chronic or degenerative lesions, up to 12 months after tenodesis (Navarro et al 2008).…”
Section: Discussionsupporting
confidence: 83%
“…Our findings are consistent with the results reported by other authors, confirming that better results are obtained when a linear probe is used for tendon examination in dogs and horses (Long and Nyland 1999;Bruce et al 2000;Kramer et al 2001;Agut et al 2009;Vilar et al 2011;Spinella et al 2013). Moreover, ultrasonographic findings confirmed the biological inactivity and biocompatibility of stainless steel AISI 316L, and revealed minimal tissue reaction of fibre tendon around it, with no chronic or degenerative lesions, up to 12 months after tenodesis (Navarro et al 2008).…”
Section: Discussionsupporting
confidence: 83%
“…No correlation was observed between the weight and size of the animals and their tendon's CSA or external size. Variations in the CSA of tendons and ligaments of clinically normal horses have been described in a number of breeds [21, 28–30]. The variation of the CSA observed could be expressed by the individual variation of CSA of the healthy tendon.…”
Section: Discussionmentioning
confidence: 99%
“…Analyses of US images use both quantitative and qualitative measurements to assess injuries, including echogenicity, fibre alignment, size, shape, margination, and tendon position. Cross-sectional area (CSA) is the most objective feature for the evaluation tendon pathology and can be assessed accurately with US [1921]. …”
Section: Introductionmentioning
confidence: 99%
“…However, the qualitative method is subjective and based on a rough estimation of the intensity of the echoes (image brightness) (14). Cross-sectional area (CSA) and mean echogenicity (ME) are quantitative methods that allow more objective evaluation of the structural integrity and size of tendons through appropriate measurements, using specific software, thickness and shape changes (13,15).…”
Section: Introductionmentioning
confidence: 99%
“…The importance of ultrasonographic measurement of CSA and ME in horses has been well established, but to the authors' knowledge, there are currently not any publications containing clearly reported information regarding quantitative ultrasonographic tendon measurements in dogs (13,15).…”
Section: Introductionmentioning
confidence: 99%